Survey analysis on the market potential of an agricultural energy management system - Christoph Bader; Eberhard Groß; Jörn Stumpenhausen; Christina Steckenbiller; Heinz Bernhardt (Frontiers in Energy Research)
The increasing demand for renewable energy and the associated reduction in the use of fossil fuels is becoming a key challenge for politics, society and science worldwide, especially in Germany. This development offers the agricultural sector the opportunity to use the energy generated itself by operating photovoltaic systems on existing agricultural buildings, wind turbines or biogas plants, regardless of the production processes used, and to supply the surplus electricity directly to the public grid as a market participant. However, intelligent electricity storage concepts and a corresponding energy management system are necessary to be able to use the existing potential at all, both to optimize internal production processes and to coordinate the varying energy demand and supply in the electricity grid. Agriculture could become an energy service provider in rural areas. The “Stable 4.0” research initiative of the Technical University of Munich and Weihenstephan-Triesdorf University of Applied Sciences has been working on the practice-oriented development of system-specific principles for the implementation of an on-farm energy management system (EMS) since 2013. Agricultural operations differ greatly from region to region, but also within their production processes, and can be expected to have varying requirements and usage profiles for the system. It is therefore of interest to what extent the industrial prototype can be used and further developed within the agricultural sector. The dissemination and use of new innovations on the market is largely determined by the users. Based on a project study with 1.057 completed online responses, the current interest of practitioners in a customized EMS can be derived. It shows that economic aspects, but also efficient self-consumption of electricity and the self-sufficiency rate are particularly important to farmers. The study also looks at the use of information channels for innovations in the field of energy and is intended to serve as the basis for a marketing concept. The influence of various production processes was also examined in the survey. Initial findings already indicate multiple potential benefits for the use of the EMS and a clear added value for the entire agricultural sector.